THE EFFECT OF PICTURE SIZE ON PREFERENCE DECISION-MAKING IN 5–6-YEAROLD CHILDREN - D.M. Xakimova; M. Mashrabova (Western European Studies, 2025)
This study explores how the visual size of pictures influences children’s decision-making and preference patterns. Twenty-five children aged 5–6 from five kindergartens in Chinabod, Uzbekistan, participated in a two -phase experiment. In the first phase, they ranked five equal-sized animal pictures from favorite to least favorite. In the second phase, the same pictures were presented in increasing sizes (turtle smallest → crocodile largest). Data were collected on favorite animal choice, time, confidence, and verbal explanations. Results showed that 56% of children changed their favorite when picture sizes differed, but only 12% arranged them by size. Although the panda became the most preferred animal in the different-size condition, most children explained their decisions through emotional reasons rather than perceptual ones. Average decision time increased slightly, and confidence decreased. These findings suggest that while visual salience can influence attention and choice, emotional preference remains th e dominant factor in early childhood decision-making.
Keywords: decision-making; visual salience; picture size